CONTROL EFFICACY AND PHYTOSOCIOLOGICAL CHARACTERIZATION OF WEEDS AS A FUNCTION OF POST-EMERGENCE HERBICIDES APPLIED TO MAIZE - DA SILVA, ALEXANDRE FERREIRA; PADRÃO, VITOR ABREU; CONCENÇO, GERMANI; GALON, LEANDRO; ASPIAZÚ, IGNACIO (REVISTA BRASILEIRA DE MILHO E SORGO, 2022)
S Studies evaluating the effectiveness of herbicides on weed control, coupled with the sustainability of the weed management system, are of great importance. The present study aims to evaluate the efficacy of post-emergence herbicides applied to maize while inferring the sustainability of the treatments employing an ecological approach. The experiment was installed in a randomized block design with four replications. The treatments consisted of the application of atrazine at the dose of 1500 g ha-1; atrazine + mesotrione at 1500 + 72 g ha-1; atrazine + tembotrione at 1500 + 100.8 g ha-1; atrazine + nicosulfuron at 1500 + 22.5 g ha-1; atrazine + glyphosate at 1500 g ha-1 + 792.5 g ha-1, in addition to weeded and infested control treatments. The herbicides were applied at the 4 leaf stage of maize. The phytotoxicity and control efficacy was assessed 7, 14, 21, and 28 days after applying treatments (DAT). In addition, a phytosociological survey of all plots was carried out in the last assessment. Herbicides did not cause phytotoxicity symptoms to the crop. However, associations of atrazine with glyphosate and atrazine with tembotrione promoted the greater effectiveness of weed control. Despite being classified as one of the treatments with better effectiveness, the association between glyphosate and atrazine, caused a more significant reduction in the diversity of the plant community, and alternative weed management practices should be applied to maize cropping fields to avoid weed selection.